2018
DOI: 10.3390/en11061512
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Use of Waste Mineral Oils as a Fuel with Organic-Based Mn Additive

Abstract: The heat values of waste mineral oils are equal to the heat value of the fuel oil. However, heat value alone is not sufficient for the use of waste minerals oils as fuel. However, the critical physical properties of fuels such as density and viscosity need to be adapted to the system in order to be used. In this study, the engine oils used in the first 10,000 km of the vehicles were used as waste mineral oil. An organic-based Mn additive was synthesized to improve the properties of the waste mineral oil. It wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Experimental data, and measurements confirming data (such as weather conditions, engine speed, electrical data of the alternator) were transferred to the datalogger made with the LattePanda development board (Figure 1). For the experimental procedure, conditions and calculations in the TS 1231 (ISO 3046 equivalent) standard were applied 39 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental data, and measurements confirming data (such as weather conditions, engine speed, electrical data of the alternator) were transferred to the datalogger made with the LattePanda development board (Figure 1). For the experimental procedure, conditions and calculations in the TS 1231 (ISO 3046 equivalent) standard were applied 39 …”
Section: Methodsmentioning
confidence: 99%
“…In this study, the first method was applied. In previous studies, metallic additives for fuels are used in the range of 4–20 μmol/L 39‐42 . Fuel properties can be improved by using these additives in such a small amount.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat loss per unit time (ḣ ) from the cylinder wall to the environment can be calculated according to Newton's cooling law [22][23][24].…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…Studied the catalytic conversion of waste engine oil to diesel engines in the presence of the nano-CeO2/SiO2 catalyst synthesized by different analytical methods and examined the physical and thermal properties of the fuel. Bülent Özdalyan and Recep (2018) found that the availability of waste mineral oils as a direct fuel in diesel engines was investigated firstly, and then the degree of improvement with organic-based Mn additive material was investigated experimentally using a diesel engine with a power of 6.4 kW. Characteristic measurements were made for a constant speed (3000 rpm) and a variable load (750 W-4.5 kW) with an alternator rated at 5 kW.…”
Section: Introductionmentioning
confidence: 99%